2018
DOI: 10.4103/jpi.jpi_52_18
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Remote Digital Frozen Sections for Cancer and Transplant Intraoperative Services

Abstract: Introduction:Whole-slide imaging (WSI) technology can be used for primary diagnosis and consultation, including intraoperative (IO) frozen section (FS). We aimed to implement and validate a digital system for the FS evaluation of cancer and transplant specimens following recommendations of the College of American Pathologists.Materials and Methods:FS cases were routinely scanned at ×20 employing the “Navigo” scanner system. IO diagnoses using glass versus digital slides after a 3-week washout period were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…On the other hand, immunohistochemical staining was standardized on a single antibody and platform as required in pembrolizumab registration study. [ 16 ] Concerning preanalytical issues, WSI has shown to be reliable for assessment of almost any type of slide, from frozen section to cytological samples[ 20 21 22 ] when proper evaluation is critical and may require the consultation of an expert. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, immunohistochemical staining was standardized on a single antibody and platform as required in pembrolizumab registration study. [ 16 ] Concerning preanalytical issues, WSI has shown to be reliable for assessment of almost any type of slide, from frozen section to cytological samples[ 20 21 22 ] when proper evaluation is critical and may require the consultation of an expert. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective validation studies have demonstrated acceptable accuracy rates (average accuracy rate - 96.7%; range 68%–100%) for TP diagnoses of FS [ Table 4 ]. [ 6 8 14 15 16 17 18 19 20 21 ] Hence, the utility of TP for primary FS diagnosis is growing as we move into an age of increasing sub-specialization and centralization of pathology services. In the year 2008, Tsuchihashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Food and Drug Administration clearance for these devices is relatively new (2017), and widespread adoption of digital pathology technology is still in its early phases. There is an increasing amount of data on validation of WSI compared to microscope viewing of glass slides, for example a recent study showed good concordance of slide interpretation of frozen sections done with glass slides/microscope compared to WSI/digital pathology workstation[ 52 ] Similar excellent intraobserver concordance between glass slides and digital pathology has been shown for routine clinical workload in surgical pathology[ 53 ].…”
Section: Ai-assisted Analysis Of Pathological and Molecular Features mentioning
confidence: 99%